Flash Sintered Potassium Sodium Niobate: High-Performance Piezoelectric Ceramics at Low Thermal Budget Processing - Serrazina, Ricardo (2022)
Alternative sintering technologies promise to overcome issues associated with conventional ceramic sintering such as high thermal budgets and CO2 footprint. The sintering process becomes even more relevant for alkali-based piezoelectric ceramics such as K0.5Na0.5NbO3 (KNN) typically fired above 1100 °C for several hours that induces secondary phase formation and, thereby, degrades their electrical characteristics. Here, an ability of KNN ceramics to be of high performance is successfully demonstrated, using an electric field- and current-assisted Flash sintering technique at 900 °C only. Reported for the first time, Flash sintered KNN ceramics have room-temperature remnant polarization Pr = 21 μC/cm2 and longitudinal piezoelectric coefficient d33 = 117 pC/N, slightly superior to that of conventional ones due to the reduced content of secondary phases. High-performance KNN ceramics Flash sintered at a low-thermal budget have implications for the development of innovative low carbon technologies, electroceramics stakeholders, and piezoelectric energy harvesters.